2014
DOI: 10.1042/bj20131681
|View full text |Cite
|
Sign up to set email alerts
|

The upstream conserved regions (UCRs) mediate homo- and hetero-oligomerization of type 4 cyclic nucleotide phosphodiesterases (PDE4s)

Abstract: Type 4 cyclic nucleotide phosphodiesterases (PDE4s) are divided into long and short forms by the presence or absence of conserved N-terminal domains termed upstream conserved regions (UCRs). We have shown previously that PDE4D2, a short variant, is a monomer, whereas PDE4D3, a long variant, is a dimer. Here, we have determined the apparent molecular weights of various long and short PDE4 variants by size exclusion chromatography and sucrose density gradient centrifugation. Our results indicate that dimerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Two pivotal actions have been evidenced for UCR1 and UCR2 domains. Firstly, they promote the long forms dimerization in vivo , involving particularly the UCR1/catalytic domain interfaces . On the other hand, UCR2, closing across the active site, blocks the access to cAMP, thus exerting a partial enzyme inhibition ,…”
Section: Introductionmentioning
confidence: 99%
“…Two pivotal actions have been evidenced for UCR1 and UCR2 domains. Firstly, they promote the long forms dimerization in vivo , involving particularly the UCR1/catalytic domain interfaces . On the other hand, UCR2, closing across the active site, blocks the access to cAMP, thus exerting a partial enzyme inhibition ,…”
Section: Introductionmentioning
confidence: 99%
“…These include the Ca 2 + /calmodulin binding domains of PDE1, the Gaf domains of PDE2, PDE5, PDE6, PDE10, PDE11 and the UCR1/2 domains of PDE4 [2,9,15,17] . Such domains have been implicated in dimer formation [35–46] .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation by protein kinase A (PKA) at a conserved site on UCR1 activates all long PDE4 isoforms (8,9). Mutation and deletion studies have shown that long forms of PDE4 are dimeric, with key dimerization interactions mediated by UCR1 and UCR2 (10,11), and that the C-terminal half of UCR2 could play a negative regulatory role (12)(13)(14)(15)(16). Access to details of these different mechanisms of control would advance our capacity to design medicines that act selectively among the PDE4 isoforms, and should also cast light on their specific intracellular functions.…”
mentioning
confidence: 99%